Safety and feasibility of toripalimab plus lenvatinib with or without radiotherapy in advanced BTC - Wang, Yunchao; Zhang, Nan; Xue, Jingnan; Zhu, Chengpei; Wang, Yanyu; Zhang, Longhao; Yang, Xu; Wang, Hao; Wang, Shanshan; Chao, Jiashuo; Yang, Xiaobo; Zhao, Haitao (Frontiers in Immunology, 2023)
Background Toripalimab shows antitumor efficacy in cholangiocarcinoma. Radiotherapy (RT) may enhance systemic responses of PD-1 inhibitors and lenvatinib. This study was designed to assess the safety and feasibility of toripalimab plus lenvatinib with or without RT in advanced BTC. Methods This study involved 88 patients with advanced BTC receiving toripalimab plus lenvatinib with or without RT from the clinical trials (NCT03892577). Propensity score matching (PSM) (1:1) analysis was used to balance potential bias. The overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and adverse events (AEs) were evaluated. Results After PSM, the final analysis included 40 patients: 20 receiving toripalimab plus lenvatinib without RT (NRT); 20 receiving toripalimab plus lenvatinib with RT. The AEs were more frequent in the RT group than in the NRT group without treatment-associated mortality. The addition of RT did not cause specific AEs. The median PFS was significantly longer with RT (10.8 versus 4.6 months, p<0.001). The median OS was 13.7 months with RT versus 9.2 months in the NRT group (p=0.008). The ORR was 35% (95% CI: 12.1-57.9) in the RT group versus 20% (95% CI: 0.8-39.2) in the NRT group. Conclusions The addition of RT may enhance the efficacy of toripalimab plus lenvatinib. Toripalimab plus lenvatinib with RT have a good safety profile without an increase in specific toxicities in advanced BTC patients.